Literature Review on Public Policy and Social Impact in Drug Rehabilitation in Indonesia - Ngaisah, Siti; Haryono, Haryono; Yuliastuti, Gusti Eka (Westscience Press, 2025)
This study examines the convergence of public policy and social impact on drug rehabilitation for addiction in Indonesia using a literature review of 13 Scopus-indexed articles. Findings highlight that Indonesia has evolved in its drug policies from punitive measures towards incorporating rehabilitative interventions, although there continue to be prevalent challenges. These include stigma, poor infrastructure, uneven policy application, and lack of inter-stakeholder coordination. Models of rehabilitation both community and faith-based also have the potential for strengthening social reintegration and reducing recidivism. The research demands policy alignment, increased investment, and stronger multi-stakeholder coordination to achieve effective and inclusive rehabilitation. Evidence emerging from this research provides a foundation for evidence-based policy and program development particular to Indonesia's socio-culture.